Evaluation of the Ministry of Education library's collection by means of citation analysis. - Tan, Joanna Yeok Ching. (2008)
The purpose of this study is to ascertain the strengths and weaknesses of the Ministry of Education Library's collection for curriculum planning, design and development using primarily citation analysis, list checking against library's holding and inter-library loan analysis as tools for collection evaluation. Citations from Teacher's Guides/ Resource Packages produced by Curriculum Specialists were used for this study.